Workplace Spirituality and the Ethical Behaviour of Project Managers - Van der Walt, Freda; Steyn, Pieter (SA Journal of Industrial Psychology, 2019)
Orientation: Despite increased interest in the topic of ethical behaviour, the unethical behaviour of individuals in various professions is increasing. In order to support professional bodies in their quest to promote ethical behaviour of professionals, one needs to consider what organisations can do to promote ethical conduct. Research purpose: The purpose of this research study was to investigate whether organisations that have spiritual values, that is, workplace spirituality, have a significant impact on the ethical behaviour of project managers. Motivation for the study: Project management as a profession has always been concerned about quality and ethics, but ethical behaviour seems to be on the increase rather than on the decrease. Therefore, it is necessary to consider factors within the organisational context that can promote ethical behaviour. Research approach/design and method: The study was quantitative in nature, and data were collected from individuals studying towards a project management qualification. A descriptive case study design was used and data were collected once-off by means of a survey. Main findings: The findings of the study indicated that workplace spirituality influenced ethical behaviour to some extent, as it promotes responsibility and fairness, which are key values of the Project Management Institute. Practical/managerial implications: If organisations adopt spiritual values and promote a spirituality-based culture, ethical behaviour could be encouraged. However, workplace spirituality should not be seen as a quick fix to reduce unethical behaviour, and unless there is honest commitment by organisational leaders to transform organisations into humanised and spirituality-based workplaces, not much will be achieved in terms of promoting ethical behaviour. Contribution/value-add: The study contributes to the literature regarding ethical behaviour and workplace spirituality.
Published Article
Keywords: Workplace Spirituality; Ethical Behaviour; Values; Project Management; Ethical Conduct